The effects of recycling process on thermal, chemical, rheological, and mechanical properties of PC/ABS binary and PA6/PC/ABS ternary blends - Kuram, Emel; Ozcelik, Babur; Yilmaz, Faruk (SAGE PUBLICATIONS LTD, 2016)
In this study, polycarbonate/acrylonitrile-butadiene-styrene (PC/ABS) and polyamide 6/PC/ABS (PA6/PC/ABS) blends were reprocessed (recycled) five times and the influences of multiple molding processes on the thermal, chemical, morphological, rheological, and mechanical properties of the recycled and virgin specimens were investigated. The impact strength, tensile properties (elastic modulus, strength, and strain at break), and flexural properties (modulus and strength) were measured to determine the mechanical properties of the blends. The rheology of the samples was evaluated via measuring the melt flow index (MFI). It was concluded that the chemical structures, melting temperatures, and thermal properties of both blends did not significantly change with recycling. From the mechanical tests, in general, it was found that increasing the number of recycling processes did not considerably alter the flexural properties and tensile strength of PC/ABS blends, but decreased their MFI and impact strength. On the other hand, the elastic modulus and tensile strength of PA6/PC/ABS decreased with the number of recycling processes, whereas MFI, flexural properties, and impact strength of the ternary blends improved.
Keywords: PC; ABS; PA6; polymer blends; injection molding; recycling; mechanical properties; ACRYLONITRILE-BUTADIENE-STYRENE; REACTIVE COMPATIBILIZERS; RUBBER CONTENT; VIRGIN; POLYCARBONATE; MORPHOLOGY; PERFORMANCE; ORGANOCLAY; Materials Science; Polymer Science